Measures of capillary permeability in acute falciparum malaria: relation to severity of infection and treatment. - Davis, T; Suputtamongkol, Y; Spencer, J; Ford, S; Chienkul, N; Schulenburg, W; White, N (1992)
Capillary permeability was investigated in 32 Thai patients aged 14-49 years who had acute falciparum malaria with use of three distinct techniques: quantitation of the urinary albumin/creatinine ratio (ACR), estimation of the transcapillary escape rate of radiolabeled albumin (TER), and retinal photography/fluorescein angiography. Fourteen patients had uncomplicated infections and 18 were severe cases. The severely ill patients had significantly higher ACRs (median, 4.8 mg/mmol; 95% confidence limits, 2.4-19.9 mg/mmol) and TERs (median, 8.3%/h; 95% confidence limits, 6.2-13.2%/h) than the uncomplicated cases (ACR: median, 2.1 mg/mmol; 95% confidence limits, 6.2-13.2%/h) than the uncomplicated cases (ACR: median, 2.1 mg/mmol; 95% confidence limits, 1.0-8.8 mg/mmol; TER: median, 5.9%/h; 95% confidence limits, 3.8-10.6%/h; P = .014 and .042). Both variables were significantly associated with biochemical indices of disease severity including total serum bilirubin levels (rs greater than or equal to 0.398, P less than .025 in each case), but there were no significant differences between ACRs and TERs among comatose and noncomatose patients with severe infections (P greater than or equal to .08). Retinopathy (hemorrhages, cotton-wool spots, capillary nonperfusion, and/or extravasation of fluorescein) was found in eight severely ill patients and in two uncomplicated cases. Fluorescein leakage was evident in six patients. Although fluorescein leakage had the strongest parametric correlation with the presence of coma relative to both ACR and TER in the full patient series (r = 0.58, P less than .01), multiple linear regression analysis indicated that concentrations of plasma lactate (t = 2.998, P = .006) and serum creatinine (t = 2.200, P = .036) were the factors responsible for this association. These data do not support a role for tissue edema in the pathogenesis of cerebral malaria but reveal an association between markers of disease severity and a generalized increase in systemic capillary permeability.